Behaviour of the Poynting vector in absorbing chiral media - Echarri, Rodolfo Manuel (2000)
The Poynting vector behaviour in chiral media with losses is studied. It is found that its mean temporal value has a component which is not on the incidence plane, while the instantaneous vector moves along the lateral surface of a cone which has its base parallel to,the incidence plane. Moreover it is found that the component which is out of the plane has opposite directions for each polarization. Finally a numerical calculation is done to analyze the dependence of this vector on the characteristic parameters.